1. Implementation Assessment of Animal Welfare on Poultry Slaughter House in Kisaran City Asahan District - Ridho Akbar Yuandi; Mulyadi Adam; Sri Wahyuni (Jurnal Medika Veterinaria, 2020)
This study aimed to assess the concept of animal welfare implementation aspects in poultry slaughterhouse at Bakti Market, Kartini Market, and Diponegoro Market in Kisaran city Asahan District Sumatra Utara Province. This research was conducted using direct observation and interview methods using a structured questionnaire based on animal welfare aspects. There were three aspects assessed in this study, which are transportation aspects, shelter aspects, and slaughter aspects. The results of this study showed that the three aspects of animal welfare in a poultry slaughterhouse in Kisaran City had not been applied positively.